GHARAR DALAM TA`ARUF ONLINE SERTA DAMPAKNYA PADA KELANGSUNGAN AKAD PRESPEKTIF HUKUM PERDATA DAN FIQIH EMPAT MADZHAB : Studi Kasus di Aplikasi Ta`aruf Online Muzz - Kamal Musthofa; Alvita Hikmatul Laily (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2022)
Ta'aruf is an effort to explore pre-marital relations between men and women in accordance with Islamic law, where the two prospective unmarried couples are expected to get to know each other, facilitated by intermediaries who know each candidate. The concept of ta'aruf is growing along with the development of the digital era. It is not only facilitated by intermediaries but ta`aruf can also be done online through websites, social media, or application. But the fraud is often occur in ta`aruf online. This research due to know more about the fraud in Muzz as an online ta`aruf app in the world. By using the datas from observation, interview, and documentation then then the researcher annalys and show them descriptively and qualiatatively. The result of this research show that there are some frauds in this online ta`aruf app; the fraud in name, profession, marriage status, religion, photo, and healty. Based on KHI pasal 72 ayat 2 and pasal 27 ayat 2 undang-undang Nomor 1 tahun 1974 tentang perkawinan (UU perkawinan), all of the frauds can be the reason to cancel the marriage if it brings disadvantages intentionally. But base on Fiqh 4 Madzhab, some of the frauds can be the reasons to cancel the marriage (fasakh nikah) but some of them just make the aim of marriage will be raiched difficultly.